All‐Dielectric Insulated 3D Plasmonic Nanoparticles for Enhanced Self‐Floating Solar Evaporation under One Sun. Issue 7 (23rd January 2023) - Wang, Yang; Ma, Haiyang; Yu, Jianyu; Li, Jinlei; Xu, Ning; Zhu, Jia; Zhou, Lin
Abstract: Plasmonic absorbers, featured by unique capability of broadband light absorption and nanoscale optical concentration, have long been regarded as ideal candidates for self‐floating interfacial solar evaporation yet suffering from low energy transfer efficiency because of poor thermal localization. In this work, by implanting an ion beam exfoliation of the continuous metallic film from the gold/nanoporous alumina template (Au/NPT), the all‐dielectric insulated plasmonic absorbers are demonstrated as efficient self‐floating interfacial solar evaporators with measured efficiency of ≈80% under one sun, which shows a ≈20% increment to conventional Au/NPT and is comparable to mainstream complicated carbon‐based evaporators with external thermal insulators. The enhanced energy transfer process can be ascribed to synergistic effect of plasmon‐enhanced solar absorption, broadband light induced thermal localization and/or insulation, as well as efficient mass transport channels. The results here would provide a new insight in underlying understanding and inspire further development of plasmonic solar thermal conversion. Abstract : All‐dielectric insulated plasmonic absorbers are presented as efficient self‐floating interfacial solar evaporators with measured efficiency of ≈80% under one sun, which shows a ≈20% increment to conventional gold/nanoporous‐template evaporators. The enhanced energy transfer process can be ascribed to synergistic effect of plasmon‐enhanced solar absorption, interfacial thermal insulation, and efficient mass transport channels.